(untitled) (Proceedings of International Educators Conference, 2024)
One of the most important tasks of the modern education system is to prepare students for a deep understanding of complex chemical processes and acquisition of practical skills. This article provides information on the use of streaming technologies and VR laboratories in the teaching of chemistry.